2014
DOI: 10.3389/fneur.2014.00165
|View full text |Cite
|
Sign up to set email alerts
|

Cortical–Subcortical Interactions in Hypersomnia Disorders: Mechanisms Underlying Cognitive and Behavioral Aspects of the Sleep–Wake Cycle

Abstract: Subcortical circuits mediating sleep–wake functions have been well characterized in animal models, and corroborated by more recent human studies. Disruptions in these circuits have been identified in hypersomnia disorders (HDs) such as narcolepsy and Kleine–Levin Syndrome, as well as in neurodegenerative disorders expressing excessive daytime sleepiness. However, the behavioral expression of sleep–wake functions is not a simple on-or-off state determined by subcortical circuits, but encompasses a complex range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 225 publications
(254 reference statements)
0
5
0
Order By: Relevance
“…The proposed association between the DMN and inwardly directed mentation 31,32 makes this finding intriguing, in the sense that it may suggest a role for the DMN as a ‘gate’ in the process of initiating sleep. Whole-brain network evidence of sleep initiation may improve our understanding of sleep disorders like insomnia where PSG criteria are difficult to apply 7,58 , and hypersomnia disorders 59 . Related hereto, a recent study identified switching instability to and from N2 sleep, together with difficulties reaching N3 sleep as important traits of insomnia 60 .…”
Section: Discussionmentioning
confidence: 99%
“…The proposed association between the DMN and inwardly directed mentation 31,32 makes this finding intriguing, in the sense that it may suggest a role for the DMN as a ‘gate’ in the process of initiating sleep. Whole-brain network evidence of sleep initiation may improve our understanding of sleep disorders like insomnia where PSG criteria are difficult to apply 7,58 , and hypersomnia disorders 59 . Related hereto, a recent study identified switching instability to and from N2 sleep, together with difficulties reaching N3 sleep as important traits of insomnia 60 .…”
Section: Discussionmentioning
confidence: 99%
“…These non-cholinergic projections largely originate from the midbrain monoamine neuron nuclei, posterior hypothalamus and basal forebrain, and make up the majority of the pathway between the NbM and the cortex (Saper et al 2010 ; 2005 ). Projections in this pathway are involved in regulating wakefulness, motivation, reward seeking, and related functions (Saper et al 2010 ; Mahler et al 2014 ; Larson-Prior et al 2014 ). Arguably, dysfunction of many of these projections could induce neuropsychiatric symptoms, including those of the CDS.…”
Section: Discussionmentioning
confidence: 99%
“…The thalamus modulates cortical arousal, influencing consciousness and regulating the cycle of sleep and wake states. It is conceived as a primary relay station of the brain encompassing the brainstem, hypothalamus, cortex, and in particular, thalamo-cortical interaction is fundamental for maintaining sleep and processing information in both REM and non-REM sleep (Larson-Prior and others 2014).…”
Section: Clinical Features and Pathogenesis Of Klsmentioning
confidence: 99%